Problems and Prospects of Growth of Sandalwood and Medicinal Plants in Karbi Anglong District of Assam with Special Reference to Diphu - Sanyal, Joyjit; Terang, Bishnu (AMC Indian Journal of Entrepreneurship, 2017)
Karbi Anglong itself is rich in natural resources because of fertility of land. The district was divided into two parts in the year 2016 and named as East and West Karbi Anglong. Many valuable trees are grown naturally in this part of the state and some are grown by people taking special initiative in different areas of the district. Apart from different areas of Karbi Anglong, Diphu is making a tremendous progress in growing different types of commercial trees in the last few years which include the plantation of rubber, teak, etc. and this wave is spreading. Along with the cultivation of rubber, in recent years people have started cultivation of the second most valuable tree in the world i.e. sandalwood. In addition, many wild plants are also found which are used in many ayurvedic medicines for the treatment of different diseases both for human beings as well as for animals. Though these are found in forest areas of Diphu, many of the wild medicinal plant are preserved in the bio-diversity cum recreation park which is located at a distance of 4 km from Diphu town on the way to Diphu-Manja road. This paper tried to focus on the cultivation of sandalwood and medicinal plants as an entrepreneurial venture in the process of economic development. Entrepreneurship occupies a significant position in the economic as well as social upgradation of a nation. A study covering 20 households in the bio-diversity cum recreation park range, located at the road side of Diphu-Manja Road was conducted. The study brought to light the positive attitude of the society towards cultivation of sandalwood and medicinal plants and the entrepreneurship culture in the town.